Tibiotalocalcaneal arthrodesis with retrograde intramedullary nailing: 29 patients’ clinical and functional evaluation()() - Caixeta, Thiago Barbosa (Rev Bras Ortop, 2014)
OBJECTIVE: To evaluate clinically and functionally the pos-operative results of patients submitted to tibiotalocalcaneal arthrodesis for the treatment of traumatic arthropathy and neuropathy. METHODS: Retrospective study of 29 patients undergoing ankle arthrodesis with intramedullary retrograde nail. All patients were evaluated for fusion time, AOFAS and VAS scores, satisfaction, and complications of surgery. The mean follow-up was 36 months (range 6–60 months). RESULTS: The union rate was 82%, and the consolidation occurred on average at 16 weeks (10–24 weeks). The pos-operative AOFAS score improved in 65.5% (average of 57.7 on neurological cases and 75.7 on cases pos-traumatic) and VAS score improved 94.1% (average of 2.3 on neurological cases and 4,2 on post-traumatic cases), and 86% of patients were satisfied with the procedure performed. Complications occurred in 11 patients (38%), including pseudoarthrosis (17.24%), infection (17.24%), material failure (13.8%) and fracture (13.8%). CONCLUSION: Tibiotalocalcaneal arthrodesis with retrograde intramedullary nail proved to be a good option for saving the ankle joint, with improvement of clinical and functional scores (AOFAS = 65.5% and VAS = 94.1%).